Eye fixations and electrodermal activity during low‐budget virtual reality embodiment. (2nd September 2020) - Krogmeier, Claudia; Mousas, Christos
Summary: As motion‐sensing devices become more accessible to consumers, it is important to understand how users experience embodiment when using these devices. In our 3 × 2 between‐groups study, we explored eye fixations and electrodermal activity (EDA) in order to more objectively understand potential interaction effects between the self‐avatar body, and the presence of a mirror within the context of low‐budget embodiment. We developed six experimental conditions concerning Body (human, mannequin, and zombie self‐avatars) and Mirror (mirror and no mirror) factors, and presented participants with a virtual environment in which they could control their self‐avatars by using HTC Vive controllers and trackers. In addition to eye fixations and EDA, we assessed self‐reported data concerning body ownership, agency, self‐location, as well as enjoyment of the experience. Our results suggest that the Body may have been more influential in eliciting body ownership than the Mirror, and that an interaction effect between Gender and Body may influence eye gaze behavior. Additionally, female participants reported significantly higher agency than males. We consider logical next steps for similar research which might elaborate upon our findings. Abstract : Top: mirror; human, mannequin, zombie. Bottom: no mirror; human, mannequin, zombie